Review of Work on Indian Tree Diseases and Decay of Timber and Methods of Control - Bagchee, K. (Indian Forester, 1952)
The paper deals with the various problems investigated during the past two decades, connected with diseases of Indian forest trees and decay of timber and discusses methods of control suitable to local conditions. In its natural habitat sal ( Shorea robusta ) is susceptible to the attack of many pirasitic fungi causing major or minor diseases. The predisposing factors have been analysed in detail and controls suggested from the mycological as well as the silvicultural points of view. Shisham ( Dalbergia sissoo ), either grown as a pure crop or in admixture with Acacia catechu or A. arabica is susceptible to root-rot diseases due to Ganodel'ma lucidum, and vascularwilt due to Fusarium sp. Controls have been worked out in the form of suitable admixture with resistant species, and protection against wound parasites. Wide spread mortality of Casuarina equisetifolia due to Trichosporium vesiculosum, a wound parasite, has been reported in some of the most thriving plantations. Manuring and deep planting to overcome malnutrition and drought, and the discontinuation of pruning and lopping are suggested as control measures. Teak ( Tectona grandis) for Olivia tectonae, Uncinata tectonae, Phyllactinea corylea and Nectaria hcemeatococcus; Gmelina arborea for Gnomonia sp. And Evodia roxburghiana for Mycosphaerella sp., have been examined. Work on Santalum album attacked by spike-disease has been reviewed. Investigations on coniferous rusts including Cronartium ribicola on Pinus excelsa, C. himalayense on P. longiJolia, C. quercuum on P. insularis and Peridermium cedri on Cedrus deodara have been completed. The controls prescribed aim at the eradication of the weed host and raising an admixture of conifers and broad leaved species in new stands. A preliminary study of the root and collar rot disease of Cedrus deodara, Pinus excelsa and Picea marinda due to Fomes annosus, Polyporus circinatus and P. schweintizii, which take a heavy toll of these conifers in the Himalayas has been made. A recent survey in the Himalayas reveals an increase in the incidence of diseases due to these fungi. The work on the timber-decaying fungi includes the study of the biology and pathology of about 250 species, of Hymenomycetes attacking both hardwood and softwood timbers. The virulence of these fungi is determined by laboratory tests on wood blocks and toxicity tests are conductted by the same methods to work out the efficacy of the various wood preservatives.